STRATEGI BLENDED LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR DAN DAYA TARIK PERKULIAHAN MAHASISWA PGPAUD - Ni Luh Ika Windayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This study aims to improve learning independence and lecture attractiveness by using a blended learning strategy for students of Early Childhood Teacher Education (PGPAUD). This type of research is a Classroom Action Research (CAR) with the Kemmis-Taggart approach. This research used blended learning tools. The research stage of each cycle includes: planning, action, observation and reflection. This research was conducted in the third semester of PGPAUD study program in STAHN Mpu Kuturan Singaraja in the academic year of 2020/2021. The subjects of this study were PGPAUD students which consisted of 12 students who took the Dance Arts Education for Early Childhood courses. The data collection methods in this CAR were observation and assignment. The data analysis in this research was descriptive analysis. The results showed that the learning independence of students in the PGPAUD study program and the attractiveness of lectures in the Dance Arts Education for Early Childhood courses increased with the use of the blended learning strategy. Initially, students' learning independence was in the poor category with a percentage of 40%, there was an increase in the first cycle with a percentage of 70% in the medium category and an increase in the second cycle with a percentage of 83% who were in the high category. The attractiveness of student lectures has also increased, initially in the low category with a percentage of 35%, increasing in first cycle with a percentage of 72.5% in the medium category, again increasing in second cycle with a percentage of 87.5% being in the very high category. The improvement in each cycle was obtained by optimizing the role of students in managing their learning activities online.Keywords: blended learning, independent learning, attractiveness